State shifts in the deep Critical Zone drive landscape evolution in volcanic terrains - Leif Karlstrom; Nathaniel Klema; Gordon E. Grant; Carol Finn; Pamela L. Sullivan; Sarah Cooley; Alex Simpson; Becky Fasth; Katharine Cashman; Ken Ferrier; Lyndsay Ball; Daniele McKay (Proceedings of the National Academy of Sciences, 2025)
Volcanic provinces are among the most active but least well understood landscapes on Earth. Here, we show that the central Cascade arc, USA, exhibits systematic spatial covariation of topography and hydrology that are linked to aging volcanic bedrock, suggesting systematic controls on landscape evolution. At the Cascade crest, a locus of Quaternary volcanism, water circulates deeply through the upper ∼ 1 km of crust but transitions to shallow and dominantly horizontal flow as rocks age away from the arc front. We argue that this spatial pattern reflects a temporal state shift in the deep Critical Zone. Chemical weathering at depth, surface particulate deposition, and tectonic forcing drive landscapes away from an initial state with minimal topographic dissection, large vertical hydraulic conductivity, abundant lakes, and muted hydrographs toward a state of deep fluvial dissection, small vertical hydraulic conductivity, few lakes, and flashy hydrographs. This state shift has major implications for regional water resources. Drill hole temperature profiles imply at least 81 km 3 of active groundwater currently stored at the Cascade Range crest, with discharge variability a strong function of bedrock age. Deeply circulating groundwater also impacts volcanism, and Holocene High Cascades eruptions reflect explosive magma–water interactions that increase regional volcanic hazard potential. We propose that a Critical Zone state shift drives volcanic landscape evolution in wet climates and represents a framework for understanding interconnected solid earth dynamics and climate in these terrains.